2019
DOI: 10.14309/ajg.0000000000000197
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Obesity on Disease Activity and Patient-Reported Outcomes Measurement Information System (PROMIS) in Inflammatory Bowel Diseases

Abstract: Background and Aims:We conducted a cohort study on the impact of obesity on disease activity and patient reported outcomes measurement information system (PROMIS) measures in the IBD Partners cohort.Methods: We performed a cross-sectional and longitudinal study within IBD Partners, an internet-based cohort of >15,000 patients living with Crohn's disease (CD) and ulcerative colitis (UC). We included adult patients with IBD, with recorded body mass index (BMI), with at least 6 months of follow-up, excluding pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 23 publications
3
41
1
Order By: Relevance
“…2,18 A recent and comprehensive analysis of patient-reported data in more than 7000 IBD patients suggests increased risk of persistent disease activity or relapse in both CD and UC patients. 32 Whilst we observed no differences with regards to disease behaviour (B1-B3 in CD) and extent (E1-E3 in UC) between obese and normal weight patients in our cohort, we found that obese CD, but not UC patients, showed increased disease activity scores compared to normal weight patients. The daily soft stool frequency was increased from a median of four times per day in normal weight patients to eight times per day in obese CD patients.…”
Section: Discussioncontrasting
confidence: 79%
“…2,18 A recent and comprehensive analysis of patient-reported data in more than 7000 IBD patients suggests increased risk of persistent disease activity or relapse in both CD and UC patients. 32 Whilst we observed no differences with regards to disease behaviour (B1-B3 in CD) and extent (E1-E3 in UC) between obese and normal weight patients in our cohort, we found that obese CD, but not UC patients, showed increased disease activity scores compared to normal weight patients. The daily soft stool frequency was increased from a median of four times per day in normal weight patients to eight times per day in obese CD patients.…”
Section: Discussioncontrasting
confidence: 79%
“…Moreover, obesity might also impair clinical response to treatment, indeed in a longitudinal study in IBD patients, obesity was not only related to higher clinical activity at baseline evaluation, assessed by using validated disease activity indexes, but also to a higher risk of relapse and remaining persistently active compared with patients with normal BMI at 12 months follow-up [61]. These findings confirm previous data showing that obesity can negatively affect response to biologic therapy in patients with ulcerative colitis [62].…”
Section: Inflammatory Bowel Disease (Ibd)supporting
confidence: 85%
“…Obesity predicts adverse clinical outcomes and treatment responses in rheumatoid arthritis, systemic lupus erythematosus and psoriasis, [88][89][90] worsens functional capacity in systemic sclerosis, 91 increases the prevalence and worsens the severity of asthma, 92 has deleterious effects in inflammatory bowel disease and multiple sclerosis, 93,94 and contributes to the progression of diabetes, non-alcoholic steatohepatitis and chronic kidney disease. [95][96][97] By acting as a broad accelerant of systemic inflammation, obesity potentiates the likelihood of heart failure (particularly HFpEF) in patients who are already prone to its development.…”
Section: Obesity As a Link Between Systemic Inflammation And Metabolimentioning
confidence: 99%